At the junction between state, nature and capital: Irrigation mega-projects in Sudan. Issue 106 (November 2019) - Bertoncin, Marina; Pase, Andrea; Quatrida, Daria; Turrini, Stefano
Abstract: This paper investigates the different ways in which the state can derive value from its control over space and non-human nature. The analysis is based on the Sudanese case and the centrality of land and water in the political ecology of the country, attested by the continual establishment of irrigation mega-projects. There are two main scenarios. In the first one, the state acts directly in the economic exploitation of natural resources; such outright involvement in the production processes can be realised with or without the involvement of private capital. In the second one, it offers preconditions to private investors by establishing a legal framework (for land concessions and exploitation rights) and by providing operative requirements (such as infrastructures and public security). In this way, the state is able to extract rents. In both scenarios the state's role inevitably changes. In the first case, it is a first-person producer of surplus value. In the second case, it collects income. These different strategies are both forms of an exercise of power that affects the organization of a territory. It is our focus to concentrate on the territorial outcomes of these two scenarios. By analysing the period from the Anglo-Egyptian Condominium to the present times, we were able to observe the changing attitude of the state regarding the exploitation of natural resources and the mobilization of capital. Our starting point is Scott's insight about the process that transforms inherited "thick" spaces into "state spaces": he defines the territorial outcomes as "thin spaces". We want to take a step further by presenting 'ultra-thin spaces', spaces that are suitable for mobile investments in the global market. In our perspective, ultra-thin spaces constitute the territorial outcome of a state which derives value by conceding control over natural resources and exploitation rights to others. This approach, taken from an historical perspective, analyses how the different relationships between state, capital and nature have had different outcomes in the territory. Even if applied to the specific Sudanese case, it serves as a means to more broadly understand this phenomenon constitutive of new global geopolitics where even the sovereignty of the state is being redefined.